Trichostatin A destabilizes HIF-2α through a VHL-independent but proteasome-dependent pathway in cancer cell lines and tumor xenografts - Yang, Qingcheng; Du, Yuzhen; Cheng, Dongdong; Zhang, Zhichang; Du, Xinhui (Bangladesh Journal of Pharmacology, 2013)
Histone deacetylase (HDACs) inhibitors are a new generation of anti-cancer agents. Little is known regarding the effect of HDAC inhibitors on HIF-2α. The effect of trichostatin A (TSA), a class I/II HDAC inhibitor, on HIF-2α protein expression was investiagted in cancer cell lines and tumor xenografts. Results showed TSA inhibited the HIF-2α protein expression in a dose-dependent manner, which was VHL-independent, but proteasome-dependent in cell lines. In tumor xenografts, TSA inhibited tumor growth and HIF-2α expression. Knocking down of HDAC6 by small RNA interfering decreased HIF-2α protein expression. HDAC6 physically interracted with HIF-2α, and HIF-2α was acetylated by TSA. TSA destabilizes HIF-2α in a proteasome dependent manner, which is unrelated to VHL, suggesting the anticancer effect of TSA is at least partially mediated by its inhibition of HIF-2α, which provides a new insight into the molecular mechanism underlying the anticancer effect of HDAC inhibitors.